The Influence of Diabetic Foot Exercise in Sensory Peripheral Neuropathy with Monofilament Test on Diabetes Mellitus Clients - Tintin Sukartini; Candra Panji Asmoro; Nandani Alifah (Jurnal Ners, 2019)
Background: Peripheral neuropathy is a long-term complication that attacks the nerves and loses the sensation of protection which affects about 50% of people with diabetes mellitus (DM). Diabetic foot exercises can help blood circulation, especially in the legs or lower limbs. This researched aimed to analyze the effect of diabetic foot exercise on sensory peripheral neuropathy in DM clients.Method: The study design used quasi-experimental pre-post test with control group. Samples were 28 respondents using purposive sampling and divided into two groups of 14 respondents each. The independent variable is diabetic foot training, and the dependent variable is peripheral sensory neuropathy. Interventions are carried out 3 times a week for 4 weeks. The research instrument was Weinstein Monofilament 10 g Semmes and a diabetic foot training checklist. Data analysis using the Wilcoxon-signed rank test and Mann Whitney test with α≤0.05.Result: The Wilcoxon-signed rank test in the treatment group showed differences in sensory peripheral neuropathy after treatment (p=0,000) and no difference in the control group (p=0.564). The Mann Whitney test results showed differences in sensory peripheral neuropathy between the treatment group and the control group after treatment p=0.039.Conclusion: Diabetic foot exercises can be used as an alternative measure to improve sensory peripheral neuropathy.